HLA-DRB1 alleles in patients with rheumatoid arthritis - L A Taukumova; I A Guseva (Научно-практическая ревматология, 2004)
Objective. To examine the distribution of HLA-DRBI alleles frequency in pts (pts) with protracted rheumatoid arthritis in Russian population. Material and methods. 44 pts with RA (ACR criteria) with a mean age 53,7 yrs (30-72), a mean disease duration 13,6 yrs (5-31) were included. 95% of pts were taken a monotherapy or combination of DMARDs. Radiographic damage assessment in wrists and foots was examined by Larsen method. HLA- DRBI typing was performed using PCR method. 135 health donors were a control group. Results. 27 RA pts had HLA-DRB*04 alleles (45,5%) , in control - in 12,6 %, respectively (p<0,0005, OR=6,3). DRBI*04 positive pts were 24 RF(+), along 12 RF(-) pts DR4-positive were 7 pts (74% versus 58%). Radiographic destruction was equally severe both in DR4(+) pts anf DR4(-) pts, 92% and 71% respectively (NS). Retrospective analysis of determination of the influence of DMARD choice showed that Amimalarics were applied at the onset of disease. At the present time Methotrexate was frequently administered both in all pts (p<0,0012) and in 12 DR4(+) pts (44%) in comparison with 3 DR4(-) pts (18%), (NS). The DR(-) pts who had moderate joint damage were taken Sulphasalazine. Combination therapy with DMARD and steroids was used more active in pts with DRB1*04 (NS). HLA-DRBI*04 had an association with factor of beginning time of DMARDs therapy (r=0,32, p<0,04) and a functional activity (r=0,35, p<0,05). Conclusion. The previously results showed that RA in Russian population is associated with a high frequency of DRBI*04 alleles and low frequency of DRBI*07 which had a protective role for disease course. HLA-DRBI*04 possibly could be included in the list of prognostic factors of RA. Large prospective long-term investigations are needed for the determination of specific genetic markers at the onset of RA that may be valuable for predicting the disease severity and selecting appropriate therapy.